DAMPAK ORIENTASI MODEL PENGUKURAN KINERJA DALAM MENINGKATKAN TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH (Studi Kasus di Kota Gorontalo) - Mattoasi, Mattoasi; Syamsudin, Rose Shamsiah (Humanus, 2015)
Performance measurement orientation model is important to be the concern to all heads of organizations, particularly in public sector organizations in providing maximum service to the community. Measurement orientation of the input will be different from those of output and outcome, especially the impacts to the community. This study intends to look at the impact of performance measurement orientation towards transparency of the reporting of local administration. The method used is qualitative by (1) analysis of literatures and some of the laws and regulations that relate to a model of performance measurement that has ever been and is being implemented in Gorontalo and (2) content analysis, by analyzing each performance report both for input oriented as well as output and outcome oriented. The results show that output and outcome oriented performance measurement model is more transparent in presenting information to the public compared to the performance measurement model that have an input orientation.Keywords: performance, performance measurement, performance measurement orientation, transparency